Postural orthostatic tachycardia syndrome in pregnancy: a case report and review of literature. (18th April 2012) - Kindinger, L; Terry, J; Syed, S; Phelan, L
Abstract : Postural Orthostatic Tachycardia Syndrome (POTS) is an autonomic condition characterised by the increase in heart rate greater than 30 beats per minute with associated orthostatic symptoms including palpitations, dizziness and syncope. Females are affected more than males, particularly during childbearing age. We report a 35 year old woman with POTS in her second pregnancy. Diagnosed four years prior to her first pregnancy, she remains under the care of an Autonomic Neurologist in conjunction with Rheumatology for her Ehlers Danlos, Haematology for a Mast cell dysfunction, and Obstetricians during pregnancy. Her resting heart rate is 80-90bpm, rising to160bpm during exacerbations. These are provoked by heat, stress, excessive eating or exercise. Moderate daily walking however improves her long term control through improving peripheral tone. Medical management of POTS in pregnancy remains unclear. Treatments are focused on rate control or peripheral vasoconstriction. She is on Midodrine, an α1-receptor agonist and sodium supplements. Reports of POTS in pregnancy are infrequent, however her experiences are typical; symptoms may worsen in the first trimester, improve in the second and third trimester, and may be significantly better post partum compared to the pre-pregnancy state. There are no long term effects of pregnancy on POTS and POTS does not present an increased risk for pregnancy. Diagnosis is important for optimising symptom control and avoiding undue concern over tachycardia in pregnancy such as bleeding or infection. Advocated mode of delivery remains uncertain. A multidisciplinary team approach with consultant led Obstetric clinics and an Anaesthetic review antenatally is recommended.